2006
DOI: 10.1523/jneurosci.1764-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alterations of White Matter Associated with Visuospatial and Sensorimotor Dysfunction in Turner Syndrome

Abstract: Turner syndrome (TS) is a neurogenetic disorder characterized by impaired spatial, numerical, and motor functioning but relatively spared verbal ability. Results from previous neuroimaging studies suggest that gray matter alterations in parietal and frontal regions may contribute to atypical visuospatial and executive functioning in TS. Recent findings in TS also indicate variations in the shape of parietal gyri and white matter microstructural anomalies of the temporal lobe. Diffusion tensor imaging and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 51 publications
(68 reference statements)
11
52
1
2
Order By: Relevance
“…This hypothesis would be consistent with findings of reduced brain activation in the parietal region during visuospatial processing (MeyerLindenberg et al, 2004). These interpretations remain to be tested in future studies, because previous studies showed increased FA as potentially reflecting both compensatory mechanisms (Holzapfel et al, 2006) and poor cognitive functioning (Tuch et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This hypothesis would be consistent with findings of reduced brain activation in the parietal region during visuospatial processing (MeyerLindenberg et al, 2004). These interpretations remain to be tested in future studies, because previous studies showed increased FA as potentially reflecting both compensatory mechanisms (Holzapfel et al, 2006) and poor cognitive functioning (Tuch et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Among the DD individuals, seven had idiopathic DD, and three had a diagnosis of fragile X syndrome, Turner syndrome, or velocardiofacial syndrome, and were diagnosed as in previous publications from our group Gothelf et al, 2005Gothelf et al, , 2007aThompson et al, 2005;Holzapfel et al, 2006;Kesler et al, 2006;Hoeft et al, 2007).…”
Section: Participantsmentioning
confidence: 98%
“…These regions are notable in that (i) they are known to be connected to the IPS by white matter tracts which are thought to be disrupted in TS (e.g. inferior and superior longitudinal fasciculus) based on diffusion tensor imaging (DTI) and sMRI data (Cutter et al, 2006; Holzapfel et al, 2006; Molko et al, 2004), and (ii) simultaneous functional abnormalities within many of these regions have been previously documented in TS during fMRI studies [(Kesler et al, 2006; Molko et al, 2003) - left intra-parietal sulcus, left supramarginal gyrus, superior and middle temporal cortices, cingulate and right inferior and middle frontal cortices during numerical reasoning].…”
Section: Discussionmentioning
confidence: 99%
“…Holzapfel et al performed neuroimaging on females with Turner syndrome in search of altered areas causing the visuo-spatial and sensorimotor dysfunction in these women (Holzapfel et al, 2006). They report changes in the left parieto-occipital region extending into the frontal lobe and bilaterally in the internal capsule extending into the globus pallidus and in the right prefrontal region.…”
Section: Discussionmentioning
confidence: 99%